1997
DOI: 10.1046/j.1365-2982.1997.d01-21.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transit time in patients with myelomeningocele

Abstract: To evaluate colonic motility in patients with myelomeningocele, the transit time of radiopaque markers was studied in 22 patients with myelomeningocele and 22 age and sex matched controls. Mean colonic transit time was significantly longer in patients than in controls (103.2 +/- 49 h versus 23.3 +/- 13 h; P < 10(-7). Thirteen of 22 patients with myelomeningocele were severely constipated. Six patients had constipation secondary to delayed colonic transit, particularly in the left colon, and seven had increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…In patients with multiple sclerosis the prevalence of colorectal dysfunction is 41% to 68%, the prevalence of constipation is 36% to 53% and depending on the de®nition used the prevalence of faecal incontinence is 3.4% to 53%. 14 ± 16,28 Several studies have demonstrated that colonic transit time is prolonged in SCI patients, 4,29 ± 31 in spina bi®da 32 and in patients with multiple sclerosis. 33,34 In supraconal SCI patients a segmental transit study showed prolonged colonic transit time involving the entire colon.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with multiple sclerosis the prevalence of colorectal dysfunction is 41% to 68%, the prevalence of constipation is 36% to 53% and depending on the de®nition used the prevalence of faecal incontinence is 3.4% to 53%. 14 ± 16,28 Several studies have demonstrated that colonic transit time is prolonged in SCI patients, 4,29 ± 31 in spina bi®da 32 and in patients with multiple sclerosis. 33,34 In supraconal SCI patients a segmental transit study showed prolonged colonic transit time involving the entire colon.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders involving spinal cord function often affect colorectal motility40 ano‐rectal sensation, and anal sphincter function. Cardinal symptoms consist of chronic constipation and fecal incontinence.…”
Section: Evaluation Of Neuropathic Bowel Dysfunctionmentioning
confidence: 99%
“…In one study [Wing et al, 2001], anorectal function determined by manometry did not predict outcome after the antegrade colonic enema (ACE) procedure. In addition to anorectal dysfunction, some children have decreased gastrointestinal motility [Pigeon et al, 1997], which is felt to be secondary to abnormal migration of nerve cells into the gut.…”
Section: Bowel Functionmentioning
confidence: 99%